Effectiveness of Plant Growth Promoting Rhizobacteria (PGPR) Bamboo Roots on the Growth of Coconut Seedlings (Cocos nucifera L.) Salak Genjah Variety - Paulus, Jeanne Martje; Runtunuwu, Stella; Rantung, Meity; Matana, Yulius (ITScience (Information Technology and Science), 2025)
Coconut (Cocos nucifera L.) is a highly valued agricultural commodity in Indonesia. The Salak Dwarf variety is particularly popular among farmers due to its short harvest period and high productivity. To further enhance its potential, the use of Plant Growth-Promoting Rhizobacteria (PGPR) is being explored. PGPR are beneficial microorganisms that act as biofertilizers, improving plant growth through mechanisms such as nitrogen fixation, phosphate solubilization, and the production of growth hormones. This study aimed to evaluate the effectiveness of PGPR derived from bamboo roots on the growth of Salak Dwarf coconut seedlings. The research also sought to determine the optimal PGPR concentration for maximizing seedling growth. The experiment was conducted at the BSIP Tanaman Palma in North Sulawesi from January to May 2024. A Randomised Block Design (RBD) was used, with six treatments and three replications, totaling 18 experimental units. The treatments included a control (P0) with no PGPR and five PGPR concentrations (30, 60, 90, 120, and 150 ml/L). The key growth variables measured were plant height, leaf number, pseudo-stem girth, and leaf width. The results showed that bamboo root PGPR significantly influenced all measured growth parameters. The study concluded that the most effective concentration for promoting the growth of Salak Dwarf coconut seedlings was 60 mL/L. This finding highlights the potential of bamboo root PGPR as a natural, sustainable biostimulant to improve coconut cultivation.